Implementasi Problem Based Learning Pada Tema Transformasi Energi Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Maulana Irsyad; Astri Sutisnawati; Luthfi Hamdani Maula (Journal on Education, 2023)
This research is intended as an effort to explain the application of the Problem Based Learning (PBL) model on the theme of energy transformation in improving teacher teaching skills, student learning activities, and students' critical thinking skills. This research was carried out on grade IV students of SDN Sukamulya through the use of research subjects totaling 22 students, through two cycles. This study contains the independent variable, namely the Problem Based Learning model, then for the dependent variable, namely the ability to think critically. This research data was analyzed quantitatively, with data collection through test and non-test techniques through the use of measuring instruments in the form of criteria tables. The results of the research on teacher skills in cycle I got a score of 75 and cycle II with a score of 90. Results of research on student learning activities in cycle I got a score of 73 and cycle II with a score of 88. Meanwhile, the results of research on critical thinking skills in cycle I got an average classical 74 with less critical criteria and predicate need guidance and cycle II worth 87 with critical criteria and good predicate. In conclusion, The PBL learning model can be useful in improving students' critical thinking skills.